The entrepreneurship SIG at the European Academy of Management : setting the base for tomorrow's challenge - Songini, Lucrezia; Gnan, Luca; Starnawska, Marzena; Raith, Matthias; Pellegrini, Massimiliano (The entrepreneurship SIG at the European Academy of Management : new horizons with strong traditions, 2024)
This third volume of the book series The Entrepreneurship SIG at European Academy of Management brings together contributions on aspects characterizing the field of entrepreneurship, such as entrepreneurial behavior and mindsets and business models, but addressed in light of some of the dynamics of change that characterize the current context, such as digitalization. Moreover, the book also discusses emerging issues in academic debate, including in the wake of the recent COVID 19 pandemic, such as resilience, and relevant business contexts, such as that of family businesses. The book valorizes different contexts and key strengths of the European perspective.